2017
DOI: 10.1039/c6ra27524a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten surface density of WO3–ZrO2 on its catalytic performance in hydrogenolysis of cellulose to ethylene glycol

Abstract: New understanding on reaction mechanism of cellulose hydrogenolysis to ethylene glycol over WO3–ZrO2 catalyst combined with Ru/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 55 publications
(58 reference statements)
2
35
0
1
Order By: Relevance
“…This disadvantage could be compensated by optimization of the catalyst preparation. In particular, the calcination temperature, which has a decisive influence on the activity and selectivity of Zr/W systems, should be optimized in further studies . This should be subject to further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This disadvantage could be compensated by optimization of the catalyst preparation. In particular, the calcination temperature, which has a decisive influence on the activity and selectivity of Zr/W systems, should be optimized in further studies . This should be subject to further research.…”
Section: Discussionmentioning
confidence: 99%
“…Good yields of lactic acid and 2,5‐hexanedione were observed with tungstated zirconia . Good yields of ethylene glycol from cellulose were obtained with a WO 3 ‐ZrO 2 catalyst in combination with Ru/C …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a partial pore blockage by nickel particle species deposited over the supports' surface during catalyst preparation is also likely . In addition, Chai et al (2017) have reported that at high calcination temperatures the SSA of tungstated zirconia declines due to the sintering of ZrO 2 , which is also accompanied by a significant rise in the tungsten surface density. The N 2 adsorption-desorption isotherms at −196 • C of the reduced catalysts are shown in Figure 1; their corresponding PSD characteristics are presented as insets.…”
Section: Textural and Structural Characterizationmentioning
confidence: 99%
“…The origin of these differences can be attributed to the existence of higher concentration of anionic defects on m-ZrO 2 than on t-ZrO 2 . The different symmetry and spacing of the OH and Zr-O bonds at tetragonal ZrO 2 and monoclinic ZrO 2 can play an important role in the dispersion of the active metal component and consequently on the properties of the catalytic systems (Chai et al, 2017;Silveira et al, 2017). Sato et al (2013) investigating the effect of the ZrO 2 phase on the structure and behavior of supported Cu catalysts for ethanol conversion, concluded that the activity of Cu/ZrO 2 catalysts is strongly dependent on the phase structure of ZrO 2 , as Cu catalysts supported over monoclinic ZrO 2 were found more active than catalysts with the same Cu surface density deposited on tetragonal ZrO 2 .…”
Section: Textural and Structural Characterizationmentioning
confidence: 99%